Oxidation of a nanostructured superalloy of high temperature. (December 2017) - Aklouche-Benouaguef, S.; Adjal, S.; Miroud, D.
Abstract: The oxidation kinetics of a nickel-based super alloy developed by powder metallurgy and used in the disks of turbine blades is investigated analytically, numerically and experimentally.The rate oxidation constant and the evolution of the forehead oxidation were determined analytically using Fick's diffusion equation. This equation is solved by the method of finite volumes and an iterative method.In the experimental part we have considered a material in the powder state and then in the compacted state. We have analyzed the behavior of the material by thermo gravimetric analysis for two periods: the transitional period when the temperature increases over time and the period where the temperature is maintained constant. The results showed that at a temperature equal to 700 ° C and forthe powder state the mass gain is equal to 0.09%. For the compacted material it is equal to 0.14%.